The essay and psychogeography: Negotiating Marxism in the essays of Iain Sinclair and Will Self. Issue 1 (1st July 2019) - Brown, Will
AbstractIn their essays for the London Review of Books (LRB), Iain Sinclair and Will Self draw on two legacies in particular ‐ that of the essays of Walter Benjamin and Theodor Adorno, and that of Psychogeography and the work of the Situationist International. This article reviews a selection of these LRB essays ‐ appearing between 2002 and 2015. It traces and analyses a dialectical tension within them ‐ inherited from Benjamin and Adorno ‐ as to the commensurability of 'the essayistic' with the delivery of serious, effective Marxist criticism; whether (as Self himself says, noting an analogous tension in the films of Patrick Keiller) they are to see their own work 'as part of a strategy of resistance to the spatial forms of late capitalism, or only as incorporations of the everyday into a bourgeois calculus of the arty-factual'. It is argued that this tension is itself not only characteristic of, but in some way fundamental to their work and its impetus, concluding with a consideration of how the essay form might offer a means of moving beyond ideology (which is the constraint of both capitalism and Marxism alike) ‐ to find a literary analogue to, and vehicle for, the imaginative spatial possibilities and practices that the psychogeographic legacy represents.